O direito fundamental social à moradia na Constituição brasileira de 1988 - Basili, Hugo de Oliveira Vieira (2018)
With this research, we sought to know the constitutional normativity of the fundamental social right to housing, which required studying the social profile of the Brazilian State to contextualize the strategies of positivation of this right in the Constitution of 1988. We traced the political and economic foundations of constitutionalism, which resulted in Constitution as a legal document, culminating the study of this point in the current framework of neoconstitutionalism. The understanding of some aspects of the theory of fundamental rights was also necessary, especially, on the double character of these rights. We further study the Constitution of 1988 in what is most pertinent to fundamental social rights and identify the conformation of a Democratic and Social State of Right. Following the research, we also study the international system for the protection of human rights, albeit briefly, but sufficient to highlight how the right to housing is treated at such a normative level. In the Brazilian constitutional order, it was found that the right to housing is expressly affirmed in several provisions, from the original text of the Constitution, through programmatic norms and through an institution of subjective public law. In this normative framework, considering the duty to promote the dignity of the human person, the prevalence of human rights and the constitutional normativity of the right to housing, we reach with the research the understanding that the Brazilian State has a duty to promote and not violate this right, which integrates the vital minimum. Hence it is demandable of the State that does not act in such a way as to interrupt the exercise of such right, in addition to the duty to promote public policies to guarantee adequate housing for all those who need it. We also analyze some recent decisions of the Brazilian Judiciary on the right to housing